Preference for STEM by adolescent girls according to their geographical location (The Journal of Psychology and Sociology, 2022)
It's critical to achieve gender equality in STEM fields. Women do, however, choose this field less frequently than men. Stereotypes about gender primarily influence this choice. However, we speculate that there may be additional factors at play in this issue, one of which we attempted to investigate in our study—geographical position. This study aims to determine whether girls' perceptions of STEM careers differ between urban and rural areas. In the study, we looked into the career interests and career choices of teenagers from both urban and rural schools. Surveys were used in the study because they were the most efficient way to gather data and cover larger areas. As a result, urban females are more interested in and engaged in STEM fields, and they are less likely to choose fields where women predominate. Additionally, less participation in STEM-related extracurricular activities was seen among both men and women, which suggests that rural schools have fewer STEM resources. We will now have a better understanding of the factors causing the gender gap in STEM fields, which has a significant impact on education policy and management. Key words: gender equality, STEM, rural areas, urban areas, high school students, career choices.